Pemerolehan Leksikon pada Anak Usia 2 Tahun - Fransisca S.O. Dedi; Tri Riya Anggraini; Awalludin Awalludin (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2022)
This study aims to describe knowing how children's ability to acquire language, seen from the acquisition of the lexicon in children aged 2 years. The data in this study is the child's speech ability after 2 years. This study used a qualitative descriptive design. The results of this study, children aged 2 years have been able to pronounce according to the language he mastered, thus children aged 2 years can say what words he got from the language where he got both from his family and the surrounding environment by using lexicon acquisition.